Pengembangan Logo Produk dan Edukasi Laporan Keuangan Pada UMKM UD. Sumber Hidup Pabrik Tahu dan Tempe Khas Kediri Kelurahan Lewirato Kec. Mpunda Kota Bima - Nur Ilah; Nurlida Hairin Nafisa; Nasyiratunnisa Nasyiratunnisa; Dina Febriyanti; Ita Purnama (Universitas 45 Surabaya, 2024)
UD’s typical kediri tofu and tempeh factory.source of life.factory owners become more aware of the importance of using logos properly for product promotion and especially product branding to avoid varios types of problems that can occur if logo use is not done well.the factory owner decided to no longer underestimate the role and importance of logos (branding) for his bussines product.As well as providing exposure regarding bookkeeping of financial reports which can be used as one of the most important education for a factory.